Pengembangan Kaidah Fikih Fatwa Ekonomi Syariah DSN-MUI - Sandy Rizki Febriadi Sanusi; Neneng Nurhasanah; Maman Surahman (Quality Assurance Institute (LPM) State Islamic University Walisongo Semarang, 2020)
The application of fiqh principles to Islamic economic issues often uses general principles outside the muamalah field, even though general fiqh rules in the muamalah field and detailed rules have been formulated. This article aims to describe the development of fiqh principles on Islamic economic fatwas issued by the DSN-MUI from 2000 to 2019. This study uses a qualitative research approach with descriptive analysis, using a library research approach. This study's results indicate that the development of fiqh principles in the DSN-MUI fatwa can be analyzed from two perspectives. First, the ten fiqh rules with the most significant number are the rules